Components and Predictors of Biological Soil Crusts Vary at the Regional vs. Plant Community Scales - Condon, Lea A.; Pyke, David A. (Frontiers in Ecology and Evolution, 2020)
Although biological soil crusts (biocrusts) occur globally in arid and semi-arid environments, most of our knowledge of biocrust cover and ecology is from a relatively small number of locations worldwide. Some plant communities are known to have high cover of biocrusts, but the abundance of biocrusts is largely undocumented in most plant communities. Using a data driven approach, we identified 16 plant communities based on plant cover from the Assessment, Inventory, and Monitoring Strategy data from the Bureau of Land Management (AIM, 5200 plots). We found that abundance of lichens and mosses varies among communities, but that both components of biocrusts are present in all plant communities. Biocrusts are indicators of two of these communities: one that is defined by high cover of mosses and basin big sagebrush and one that is defined by high cover of lichens and shadscale saltbush. Using non-parametric multiplicative regression, we evaluated a suite of abiotic and disturbance variables to assess the degree to which climate and soils are associated with the abundance of lichens and mosses at the regional scale. At the regional scale, soil depth and maximum vapor pressure deficit were found to be strongly associated with the abundance of lichens and January minimum temperature dictated the abundance of mosses. At the scale of plant communities, community specific metrics of soil and climate were better able to explain the abundance of biocrusts. Given our demonstration of the presence of biocrusts across the western US, we hope to call attention to the need to include biocrusts in studies on ecosystem function given their arguably stronger association with climatic variation, direct association with soils, and their contribution to ecosystem functions that are not solely maintained by vascular plants.